MIOCARDIOPATIA ACROMEGÁLICA EM UMA POPULAÇÃO ALTAMENTE MISCIGENADA: O EIXO GH/IGF-I É RELEVANTE? - Nascimento, Gilvan Cortês (2012)
Background: A specific acromegaly-related cardiomyopathy has been described in the literature, largely in Caucasians, which is independent of other risk factors, mainly hypertension. Objective: The aim of this study was to assess the cardiac changes in an extensively admixed acromegalic population and also the relevance of the aetiopathogenic factors involved, such as disease activity and hypertension. Methods: In a cross-sectional design, 37 acromegalic patients (20 brown, 14 blacks and 3 whites) and 74 controls matched by age, gender and hypertension were evaluated. Cardiac morphology and function were addressed using echocardiography parameters. Results: The mean age of patients was 46.9 ± 12.8 years, with 67.6% being female and 43.2% hypertensive. The prevalence of left ventricular hypertrophy (LVH) between acromegalics was 56.8% versus 10.8% in the controls (p< 0.001). About 86% of patients with LVH had active disease (p = 0.023). Logistic regression revealed that disease activity presented a stronger association (OR = 5.925; CI = 1.085 32.351; p = 0.040) with LVH than hypertension (OR = 3.237; CI = 0.702 14.924; p = 0.132). Most acromegalics (51.4%) presented with diastolic dysfunction that directly correlated with age and with blood pressure levels and did not correlate with the percentage of upper limit of the normal range of IGF-I (% ULNR-IGF-I). Systolic function was not affected. When black acromegalics were compared to brown ones, no statistically significant differences were observed. Conclusion: In conclusion, chronically hyperactive somatotropic axis remains as an independent and determining factor in the development of LVH, as it is more associated with this condition than hypertension in a largely admixed population with a high prevalence of blacks.